Industrial capitalisation and spatial transformation in Chinese cities: Strategic repositioning, state-owned enterprise capitalisation, and the reproduction of urban space in Beijing. (November 2015) - Hu, Fox ZY
This study examines the urbanisation of capital in the context of a socialist economy undergoing profound market transition. It identifies the dynamics of state capital as a 'missing link' in understanding the variegated forces shaping Chinese cities through a case study of Beijing – China's capital city. Contrary to the popular perception of the rolling back of state-owned enterprises (SOEs) as a natural outcome of capital switching from a declining primary circuit to a booming secondary circuit, this empirical study of urban transformation in the Beijing metropolis identifies an intriguing trajectory of 'capitalisation without privatisation' whereby the commodification of the land and housing market has been accompanied by a growing share of capital assets under the ownership control of SOEs and a spatial concentration of state capital toward the city centre since the turn of the new century. The development experience centred on the capitalisation of SOEs is shown to be reflective of the new strategic vision to remake Beijing as a national hub of corporate control and the persistent syndrome of soft budget constraint characterising SOEs under a reformed management system that prioritises operational scale and asset appreciation. The new dynamics of state capital in Beijing is found to be associated with eviscerated domestic private investment and the spatial redistribution of rural–urban migrants towards the urban fringe. The case study has implications for ongoing inquiries into the urbanisation of capital in transitional urban China and points to the need to pay adequate attention to the growth and resilience of state capital in the Chinese 'game' of landed-property production and capital circulation.